The Hong Kong advantage - Enright, Micheal L. (Oxford University Presss, 1997)
With its rapidly approaching transition from British to Communist Chinese rule, the "future of Hong Kong" has been a frequent story for news reporters in both the East and the West. But the July 1st transfer of power has been seen mostly as a political event, with virtually no analysis of the economic future of one of the world's most important business centers. Now, in The Hong Kong Advantage, readers have the conclusions of a year-long study of the competitiveness of Hong Kong, in a volume that sheds light on both the colony's profitable past and its prospects in coming years.